2022
DOI: 10.1021/acschemneuro.1c00548
|View full text |Cite
|
Sign up to set email alerts
|

Anti-α-synuclein Toxicity and Anti-neurodegenerative Role of Chrysin in Transgenic Caenorhabditis elegans Models of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most progressive neurodegenerative disorder of the central nervous system in the elderly, causing motor impediments and cognitive dysfunctions. Dopaminergic (DA) neuron degeneration and α-synuclein (α-Syn) accumulation in substantia nigra pars compacta are the major contributors to this disease. At present, PD remains untreatable with a huge burden on the quality of life. Therefore, we attempt to explore novel treatment strategies by detecting effective drugs that stop or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The deposition of Aβ, polyQ, and α-syn caused by proteostasis imbalance mainly gave rise to neurodegeneration and cognitive decline in NDs. , We previously found that 180 μM CL could significantly delay the occurrence of paralytic behavior in Aβ 1‑42 acute aggregation nematode model CL4176 and polyQ age-related aggregation model AM140 . However, the effect of CL on neuronal homeostasis, proteostasis balance, and mitochondrial homeostasis in NDs was not yet clear, so CL at the same concentration was conducted in this study.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The deposition of Aβ, polyQ, and α-syn caused by proteostasis imbalance mainly gave rise to neurodegeneration and cognitive decline in NDs. , We previously found that 180 μM CL could significantly delay the occurrence of paralytic behavior in Aβ 1‑42 acute aggregation nematode model CL4176 and polyQ age-related aggregation model AM140 . However, the effect of CL on neuronal homeostasis, proteostasis balance, and mitochondrial homeostasis in NDs was not yet clear, so CL at the same concentration was conducted in this study.…”
Section: Resultsmentioning
confidence: 89%
“…Further, to deeply investigate the effect of CL on cognitive impairment in HD, the food-sensing ability assay and learning association capacity test were performed on the HA759 strains. Since nematodes exhibited a “basal slowing response” when perceiving food, the changes in basal slowing response levels were measured to assess polyQ mediated cognitive impairment in HD nematodes. , The result revealed that CL treatment obviously improved the HA759 worms’ basal slowing behaviors by 36.15% compared to the control (Figure E). Second, nematodes will associate sodium chloride (NaCl) with hunger and deliberately avoid NaCl after being starved in the presence of NaCl .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysin may also confer neuroprotection, slowing the pace of cognitive decline in neurodegenerative disorders such as Alzheimer’s disease and Parkinson’s disease [ 26 ]; the latter has been demonstrated in vivo using transgenic Caenorhabditis elegans disease models [ 66 ]. The administration of 5 and 20 mg/kg chrysin every 28 days also increased sucrose consumption and reduced immobility during the tail suspension test in female C57B/6J mice exposed to chronic unpredictable mild stress as a model of depression [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used C. elegans to explore the potential anti‐Parkinsonian's activity and mechanisms of natural products. For example, chrysin, a flavonoid derived from passion flowers, has been shown to have anti‐Parkinsonian activity which links to its antioxidative role in the transgenic C. elegans PD model (Muhammad et al, 2022). Chlorogenic acid and β‐amyrin have been reported to improve Parkisonian's effect in transgenic C. elegans PD model which are associated with autophagy‐related mechanisms (He et al, 2021; Wei, Chang, & Liao, 2017).…”
Section: Introductionmentioning
confidence: 99%